Productivity and effective demand: Assessing the disaggregate public spending - Josué Zavaleta; Moritz Alberto Cruz Blanco (Investigación Económica, 2019)
In this paper, we attempt to support the argument regarding the endogeneity of productivity to effective demand. Unlike most of the works on the topic, we focus on the role that both public investment and public consumption have on productivity. We suggest, at the theoretical level, that public investment has unambiguously positive effects on productivity, whereas the effect of public consumption is ambiguous, being not necessarily large or positive. Our econometric results, using data of selected Latin American economies, support the previous argument. The policy recommendation that follows from these results is that an expansionary fiscal policy based on public investment can indeed enhance the productivity evolution and consequently economic growth and development.
Keywords: O11; O23; O47; 330; Productivity; aggregate demand; public spending; Latin America